What are the clinical symptoms and physical signs for non‐small cell lung cancer before diagnosis is made? A nation‐wide multicenter 10‐year retrospective study in China. (31st May 2019) - Xing, Pu‐Yuan; Zhu, Yi‐Xiang; Wang, Le; Hui, Zhou‐Guang; Liu, Shang‐Mei; Ren, Jian‐Song; Zhang, Ye; Song, Yan; Liu, Cheng‐Cheng; Huang, Yun‐Chao; Liao, Xian‐Zhen; Xing, Xiao‐Jing; et al.
Abstract: Background: Most lung cancer patients are diagnosed after the onset of symptoms. However, whether the symptoms of lung cancer were independently associated with the diagnosis of lung cancer is unknown, especially in the Chinese population. Methods: We conducted a 10 years (2005‐2014) nationwide multicenter retrospective clinical epidemiology study of lung cancer patients diagnosed in China. As such, this study focused on nonsmall cell lung cancer (NSCLC). We calculated the odds ratios (ORs) for variables associated with the symptoms and physical signs using multivariate unconditional logistic regressions. Results: A total of 7184 lung cancer patients were surveyed; finally, 6398 NSCLC patients with available information about their symptoms and physical signs were included in this analysis. The most common initial symptom and physical sign was chronic cough (4156, 65.0%), followed by sputum with blood (2110, 33.0%), chest pain (1146, 17.9%), shortness of breath (1090, 17.0%), neck and supraclavicular lymphadenectasis (629, 9.8%), weight loss (529, 8.3%), metastases pain (378, 5.9%), fatigue (307, 4.8%), fever (272, 4.3%), and dyspnea (270, 4.2%). Patients with squamous carcinoma and stage III disease were more likely to present with chronic cough ( P < 0.0001) and sputum with blood ( P < 0.0001) than patients with other pathological types and clinical stages, respectively. Metastases pain ( P < 0.0001) and neck and supraclavicular lymphadenectasis ( P = 0.0006) were more likely to occur in patients with nonsquamous carcinoma than in patients with other carcinomas. Additionally, patients with stage IV disease had a higher percentage of chest pain, shortness of breath, dyspnea, weight loss, and fatigue than patients with other stages of disease. In multivariable logistic analyses, compared with patients with adenocarcinoma, patients with squamous carcinoma were more likely to experience symptoms (OR = 2.885, 95% confidence interval [CI] 2.477‐3.359) but were less likely to present physical signs (OR = 0.844, 95% CI 0.721‐0.989). The odds of having both symptoms and physical signs were higher in patients with late‐stage disease than in those with early‐stage disease ( P < 0.0001). Conclusions: The symptoms and physical signs of lung cancer were associated with the stage and pathological diagnosis of NSCLC. Patients with squamous carcinoma were more likely to develop symptoms, but not signs, than patients with adenocarcinoma. The more advanced the stage at diagnosis, the more likely that symptoms or physical signs are to develop. Further prospective cohort studies are needed to explore these results. Abstract : This is a nation‐wide multicenter 10‐year cross‐sectional study in China. This paper tried to objectively examine the symptoms and physical signs in lung cancer patients, and determine whether lung cancer symptoms were independently associated with diagnosis. We found that the symptoms and physical signs were associated with stage and pathologic diagnosis of NSCLC.